A layered 2D triaminoguanidine–glyoxal polymer and its transition metal complexes as novel insensitive energetic nanomaterials. Issue 47 (16th November 2016) - Yan, Qi-Long; Cohen, Adva; Chinnam, Ajay K.; Petrutik, Natan; Shlomovich, Avital; Burstein, Larisa; Gozin, Michael
Abstract : A new member of the 2D carbon–nitrogen-rich family of nanomaterials was synthesized by polycondensation of triaminoguanidine hydrochloride with glyoxal. This new polymer (TAGP) and its transition metal complexes (TAGP–Ms) were found to be energetic and insensitive. Abstract : A new member of the 2D carbon–nitrogen-rich family of nanomaterials was synthesized by polycondensation of triamino-guanidine hydrochloride with glyoxal. The obtained polymer (TAGP) has a carbon-to-nitrogen ratio of 3 : 4, identical to a ratio found in carbon nitrides. Our analysis showed that TAGP has a layered 2D network-type structure. TAGP is dispersible in polar organic solvents and forms stable complexes with various transition metal ions (TAGP–Ms). TAGP and most TAGP–Ms were found to exhibit properties of insensitive Energetic Materials (EMs), where TAGP shows a very low sensitivity to impact ( I m = 71.7 J) and to friction (>352.8 N). TAGP has also higher nitrogen content than all currently used energetic polymers, including glycidyl azide polymer [GAP], poly(3-nitrato-methyl-3-methyloxetane) [poly-NIMMO], and poly(glycidyl nitrate) [poly-GLYN]. Velocity of detonation of TAGP (6657 m s −1 ) was calculated to be significantly higher than that of azide-containing GAP and comparable to that of the nitrate ester-based poly-GLYN. In our perspective, TAGP is also an example of a modular and combinatorial approach in which high nitrogen-content aminoguanidine derivatives, reacted with amine-reactive low-carbon-content or energetic crosslinkers, can produce novel energetic polymers with tuneable properties and performance. The properties of the aminoguanidine-based EPs could be even further modified and tuned by coordination of transition metal ions. Our novel TAGP and TAGP–M energetic nanomaterials have great potential to be used in solid propellants and in energetic formulations and composites as new generation energetic binders and combustion catalysts.